Antioxidant activity in selected local vegetables / Sumathi a/p Murti - Murti, Sumathi (2011)
A free radical is any atom or molecule that has a single unpaired electron in an outer shell and its damage is closely associated with oxidative damage. Oxidative damage by free radicals in the human body plays an important causative role in disease initiation and progression. Antioxidants provide a measure of protection that slows the process of oxidative damage. In this study, crude petroleum benzene, chloroform, methanol and water extracts of Allium tuberosum (garlic chives), Apium graveolens (L.) (celery), Ipomoea batatas (L.) (sweet potato leaves), Murraya koenigii (L.) (curry leaves), Psophocarpus tetragonolobus (winged bean), and Sauropus androgynus (sweet leaves) were evaluated for antioxidant properties using bioassays namely 1,1-diphenyl-2- picrylhydrazyl (DPPH) radical scavenging assay, reducing power assay, metal chelating assay, haemolysate catalytic activity and lipid hydroperoxide assay. In the DPPH assay, petroleum benzene and chloroform extract of Murraya koenigii showed good free radical scavenging activities (IC50 = 21.5 µg/ml and 22.5 µg/ml respectively) when compared with standard ascorbic acid (IC50 = 3.75 µg/ml). IC50 is the concentration at which 50% of DPPH radicals are inhibited. In the reducing power assay, chloroform extract of Murraya koenigii showed strong reducing powers with absorbance value of 1.833 ± 0.003 when compared with standard butylated hydroxyanisole (BHA) with absorbance value of 2.625 ± 0.004 at 1 mg/ml. In the metal chelating assay, methanol extract of Murraya koenigii showed the highest metal chelating capacity of 88.60 ± 0.20% at 1 mg/ml when compared to ethylenediaminetetraacetic acid (EDTA) which was 98.63 ± 0.13%. In the haemolysate catalytic activity, water and chloroform extract of Psophocarpus tetragonolobus; methanol and chloroform extract of Ipomoea batatas; and chloroform extract of Murraya koenigii showed strong H2 O2 reducing activities of 98.00 ± 0.16%, 92.53 ± 0.99%, 94.03 ± 0.18%, 90.79 ± 0.71% and 87.36 ± 0.77% respectively at 200 µg/ml while the standard absorbance by unblocked catalase is 99.95 (0.949) ± 0.02%. In the lipid hydroperoxide assay, methanol extract of Ipomoea batatas showed highest hydroperoxide value of 3.079 nmol whereas methanol extract of Apium graveolens showed lowest hydroperoxide value of 0.329 nmol at 25 nmol in comparison with hydroperoxide value of the lipid hydroperoxide standard which was 4.839 nmol obtained at 5 nmol. Thin layer chromatography (TLC) were carried out on four active crude extracts namely crude chloroform and petroleum benzene extract of Murraya koenigii, crude water extract of Psophocarpus tetragonolobus and Apium graveolens to screen secondary compounds present through different type of visualisation. A spot under shortwave UV light and iodine vapour visualisation, orange colour deposition in Dragendorff’s reagent test and pink colour spot on TLC plate from sulphuric acid visualisation in all four active crude extracts indicates the presence of organic compounds, unsaturated carbon bonds, alkaloid compounds and oxidisable components, respectively. The presence of these organic compounds, unsaturated carbon bonds, alkaloid compounds and oxidisable component found in the selected vegetables may be linked to the high anti-oxidative activities observed; hence its dietary consumption may be beneficial for general health as well as disease prevention.